The first record of Orthocis Casey (Coleoptera: Ciidae) from the andean region, with the description of a distinctive new species - Lopes-Andrade, Cristiano (Zoological Science, 2010)
Orthocis Casey is recorded for the first time from the Andean Region, with the description of O. elguetai sp. nov., for which diagnostic characters and details on the male genitalia and other external morphological structures are provided. One record of the new species, from Punta Espora (Chile, higher latitude than 52°S), constitutes the southernmost record of the family Ciidae in the world, and the first in the Subantarctic subregion. A brief discussion on morphological similarities to other species in the genus is also provided.
Keywords: Tenebrionoidea; Beetle; Central Chile; Subantarctic; Subpolar; Taxonomy